PENGEMBANGAN LKPD BERORIENTASI INKUIRI TERBIMBING PADA MATERI MOMENTUM, IMPULS, DAN TUMBUKAN UNTUK SISWA SMA/MA KELAS X - Rahmy Novia; Hufri Hufri; Letmi Dwiridal (Universitas Negeri Padang, 2017)
This research is motivated that the teaching materials used can not activate the students. The teaching materials used are printed materials containing materials, sample questions and evaluation. These teaching materials make learners memorize the formula instead of mastering the concept. This study aims to produce products such as CSP and LKPD oriented guided inquiry on a matter of momentum and impulse in Physics valid, practical, and effective. This research is a research development (research anddevelopment) using 4D development model. The model consists of four phases: define (definition), stage design (design), develop phase (development), and disseminate stage (dissemination). However, this study is only done until the stage of development (development). The data of the research are analyzed by qualitative and quantitative analysis. Based on the research that has been done, the product produced in the form of RPP and LKPD oriented guided inquiry. Product research is categorized as very valid aspects and LKPD completeness RPP, RPP eligibility and LKPD contents, use of language and LKPD RPP, and kegrafisan LKPD using guided inquiry learning model component with an average value of 93.4 to 93.7 for the RPP and LKPD. Products are categorized very practical research by teachers with an average value of 88.4 to 86.9 for the RPP and LKPD, as well as practical by learners with an average value of 82.9. Product research is also effective in improving learners' test results based on comparative testing correlates with the acquisition t_hitung = -14.74 and T_ (table) = 1.7, so t calculate <t table (table), which means that this LKPD effective for use in learning.